Harnessing CURATE.AI for N‐of‐1 Optimization Analysis of Combination Therapy in Hypertension Patients: A Retrospective Case Series (Adv. Therap. 10/2021). Issue 10 (20th October 2021) - Truong, Anh T. L.; Tan, Lester W. J.; Chew, Kimberly A.; Villaraza, Steven; Siongco, Paula; Blasiak, Agata; Chen, Christopher; Ho, Dean
Abstract : In article number 2100091, Agata Blasiak, Christopher Chen, Dean Ho, and co‐workers demonstrate a promising application of CURATE.AI – a scalable, mechanism‐independent and indication‐agnostic artificial intelligence platform, to rapidly predict antihypertensive treatment responses and identify optimal, personalized doses for improved outcomes.